Rainwater harvesting for supplemental irrigation of onions in the southern dry lands of Ethiopia - Assefa, S.; Biazin, B.; Muluneh, A.; Yimer, F.; Haileslassie, Amare (Elsevier, 2016)
Agricultural water scarcity is a major limiting factor for crop production in dry land regions of sub-Saharan Africa (SSA). Despite notable efforts of developing macro-catchment rainwater harvesting (RWH) techniques, few studies have evaluated the performance of RWH for deficit supplemental irrigation of crops. We examine the agro-meteorological risks such as late onset, early cessation, overall low rainfall amounts and long dry spells during the growing season and evaluate the potential of macro-catchment RWH for supplemental irrigation of onion in the southern dry lands of Ethiopia. Field experiments were undertaken during 2012 and 2013 to evaluate the effects of 50% ETc, 75% ETc and 100% ETc irrigation levels on yield and water productivity of onion during dry and wet seasons. The harvestable yield and water productivity of onion under 75% ETc irrigation were not significantly lower than that under 100% ETc irrigation during both the dry and wet seasons. Thus, deficit supplemental irrigation of onion at 75% ETc can be implemented with macro-catchment RWH to reduce the risks of crop failure and significant yield declines in dryland areas.